PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN SAK- EMKM - Nelly Prima Putri; Irma Andriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
One of the obstacles faced by Micro, Small and Medium Enterprises (MSMEs) is financial recording and reporting. To make it easier for MSMEs to record and report finances, DSAK issues SAK-EMKM. Arsyila skin crackers are one of the MSMEs that have not recorded and reported finances. Based on this, researchers conducted research with the aim of knowing and compiling SAK-EMKM-based financial reports on the Arsyila skin cracker business. Data collection techniques use field research, while data analysis techniques integrate data into categories, detailing and compiling data. The results showed that Arsyila's skin crackers had not been able to record and report finances.Keywords: UMKM, Financial Report, SAK-EMKM.